219k views
1 vote
Step 1: ax2 + bx + c = 0 Step 2: ax2 + bx = −c Step 3: Step 4: Step 5: Step 6: Step 7: Step 8:

User Sigmaxf
by
5.0k points

2 Answers

5 votes

Answer:

B D A C

Explanation:

Edge 2021

User Matthew Fellows
by
5.2k points
1 vote

Solution :

Given a quadratic equation :


ax^2+bx+c = 0

Step 1 :
ax^2+bx+c = 0

Step 2 :
ax^2+bx=-c

Step 3 :
$x^2+(b)/(a)x = -(c)/(a)$

Step 4 :
$x^2+\left((b)/(2a)\right)^2=\left((b)/(2a)\right)^2\left((-c)/(a)\right)$

Step 5 :
$\left(x+(b)/(2a)\right)^2=\left((b)/(2a)\right)^2\left((-c)/(a)\right)$

Step 6 :
$\left(x+(b)/(2a)\right)=\sqrt{\left((b)/(2a)\right)^2\left((-c)/(a)\right)$

Step 7 :
$x=\sqrt{\left((b)/(2a)\right)^2\left((-c)/(a)\right)} - (b)/(2a)$

Step 8 :
$x= (-b \pm √(b^2-4ac))/(2a)$

Thus the derivation for finding the roots of a quadratic equations.

User Ezenhis
by
4.5k points